2018
DOI: 10.6007/ijarbss/v8-i12/5445
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Food Security and Health Among Indigenous People in Malaysia

Abstract: This article will discuss about domestic and international research on food security and health. Based on the discussion in the past review of the work, there are various factors that affect the discomfort of food. These include physical, social and economic aspects. Threats to the discomfort of these food will ultimately affect the physical and mental health of humans, thereby affecting human capital productivity. Therefore, the risk factors of food disorders should be controlled and overcome to ensure a heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…As such, efforts to introduce ICT to the community must be accompanied by measures to address this issue, such as providing language training or developing localized digital content in the Temiar language. The imperative to tackle the issue of illiteracy within rural communities arises from the need to foster social progress, as noted by Rosniza Aznie et al (2018). Failure to address this weakness may limit the potential benefits of ICT implementation in the community and lead to further marginalization of the Orang Asli people in the broader Malaysian society.…”
Section: Illiteracy and Language Limitationmentioning
confidence: 99%
“…As such, efforts to introduce ICT to the community must be accompanied by measures to address this issue, such as providing language training or developing localized digital content in the Temiar language. The imperative to tackle the issue of illiteracy within rural communities arises from the need to foster social progress, as noted by Rosniza Aznie et al (2018). Failure to address this weakness may limit the potential benefits of ICT implementation in the community and lead to further marginalization of the Orang Asli people in the broader Malaysian society.…”
Section: Illiteracy and Language Limitationmentioning
confidence: 99%
“…1 Previous studies have demonstrated that the aborigines are a vulnerable and marginalized community as they had poor nutritional and health status compared to other major ethnicities (Malays, India, and Chinese) in Peninsular Malaysia. [1][2][3][4] Obesity is a global health issue associated with various health problems, including cardiovascular diseases, type 2 diabetes mellitus (T2DM), and several cancers. 5 According to the World Health Organization, more than 650 million individuals aged 18 and above are obese.…”
Section: Introductionmentioning
confidence: 99%
“…The Orang Asli (OA), aboriginal people in Peninsular Malaysia comprised of 0.7% of the total Malaysian population (~31 million) in 2018 (latest update), which represent a minor population in Peninsular Malaysia 1 . Previous studies have demonstrated that the aborigines are a vulnerable and marginalized community as they had poor nutritional and health status compared to other major ethnicities (Malays, India, and Chinese) in Peninsular Malaysia 1–4 …”
Section: Introductionmentioning
confidence: 99%
“…Aboriginal people in peninsular Malaysia only comprises 0.7% of the total population, which represent a minor population in peninsular Malaysia (Shah et al, 2018). However, previous studies have demonstrated that the aborigines are a vulnerable and marginalised community as they had poor nutritional and health status compared to other major ethnicities in peninsular Malaysia (Hasni et al, 2018;Shah et al, 2018;Su Pei et al, 2018;SyedHussain et al, 2017), and this mainly includes the aboriginal children (Cordelia et al, 2019;Murtaza et al, 2018Murtaza et al, , 2019Murtaza et al, , 2019Wong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%